Translation of exercise test responses to exercise training in a clinical setting - Menke, M. L. (My University)
The Talk Test (TT) is a subjective sub-maximal exercise test based on a subjects' ability to speak comfortably during exercise and has been of proven value for exercise prescription. This study was designed to test the hypothesis that responses observed during the TT could be reduced/translated and used to define absolute training intensity in clinical populations.
Keywords: Testing.; Physical fitness.; Exercise physiology.; Physical Exertion.; Exercise test.